Challenges in the Use of a Support Tool with Automated Review in Student Learning of Programming Courses - Palominos-Villavicencio, F; Diaz-Munoz, H (Elsevier B.V., 2018)
Computer programming learning requires the acquisition of skills to design algorithms. The level of achievement of these skills depends on the student s effort involved to develop a program, as well as the final quality of the product. The level of skills that students achieve in programming courses is diverse, being able to observe significant differences in the degree of effectiveness of the solutions, as well as in the students learning development time. This paper describes a pilot experience aimed at measuring the incidence of focused practical activities assigned by the teacher through a CMS, as well as the self-regulation carried out by them. These aspects were measured and based on indicators derived from the activities carried out by the students in the CMS. The results are not statistically conclusive regarding the qualifications; however, the experience shows that it significantly improves the information available to the teacher and the student: (1) It provides the teacher with information regarding the ability of each student to solve different types of problems, at different moments during the course directly. (2) It allows the teacher to recommend activities or exercises tending to improve students learning results, and (3) It provides the student with immediate feedback of the solution developed, to correct it when appropriate. © 2018 The Authors. Published by Elsevier B.V.